Relevansi Pendidikan Agama Islam Dalam Menghadapi Tantangan Modern - Sufhariyanto , Ahmad; Alkausar, Alkausar; Amri, Amri (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
Islamic religious education in facing modern challenges is a significant issue in the context of today's development of society. Technological revolution, religious pluralism, changing values, consumerism, and secularization are some of the challenges that affect the understanding and practice of Islamic religious education. Therefore, this study aims to discuss the understanding and practice of Islamic religious education in dealing with these challenges in the modern era. This study uses a descriptive-analytical approach through literature review of journals, articles and related literature. The three main sub-topics discussed in this article are: (1) Understanding and practice of Islamic religious education in dealing with religious pluralism in the modern era, (2) Understanding and practice of Islamic religious education in facing the technological revolution in the modern era, and (3) Understanding and practice of Islamic religious education in the face of changing values, consumerism and secularization in the modern era